PENGARUH MATA KULIAH KEWIRAUSAHAAN DALAM MENINGKATKAN KETERAMPILAN BERWIRAUSAHA MAHASISWA PENDIDIKAN FISIKA - Westri Andayanti (Bajang Institute, 2024)
This study aims to evaluate the impact of the entrepreneurship course on the entrepreneurial attitudes and skills of students in the Physics Education program. As the demand for graduates who are not only academically competent but also possess entrepreneurial spirit increases, the role of entrepreneurship education becomes more crucial. This research utilized a survey method and quantitative data analysis involving 60 Physics Education students from a university in Indonesia. The findings indicate that the entrepreneurship course has a positive and significant effect on enhancing students' understanding of business concepts, fostering creativity, and sharpening entrepreneurial skills. Therefore, it is recommended that this course be strengthened in the Physics Education curriculum to better prepare students for the challenges of the job market.